A Novel M-SEPIC DC-DC Converter for BLDC Pumping System with Active PFC using ANFIS Controller - Vamshi Krishna Varma Kshatriya; Ram Kumar A (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
An exigent consumer related concerns confronted due to utilization of massive front-end AC-DC rectifier in a grid-tied BLDC pumping system. Harmonic distortions are acquired, which prompts the disruption of power quality at utility grid system due to AC-DC conversion. Several factors for enhancing power-quality concerns are ameliorate the grid power-factor along with reduction of harmonic distortions, tightened regulation of DC output voltage. In this way, the DC-DC boost converter plays a unique role; operated in Continuous Conduction Mode. Based on summarizing advantages & disadvantages of classical DC-DC converters, a single switch high voltage gain M-SEPIC DC-DC converter is more suggestive for water pumping system due to non-existence of coupled inductors, low switching loss, low di/dt stress, high efficiency, compact structure, low cost, etc. This work proposes the novel M-SEPIC DC-DC converter fed brushless-DC motor drive is controlled by voltage source inverter and powered by single-phase grid system with improved power-quality features. Moreover, Adaptive Neuro-Fuzzy Inference System is recommended for prediction of optimal switching states to amplify the BLDC motor speed and torque-ripple depreciation. The effectiveness of the proposed scheme is validated under constant speed situations by real-time operating conditions which are evaluated by Matlab /Simulink tool; and simulation results are conferred with attractive comparisons.